High-resolution spectroscopic studies of random strains in ferroelastic domains in a LaAlO3:Tm3+ single crystal - K.N. Boldyrev; N.M. Abishev; I.E. Mumdzi; S.I. Nikitin; B.Z. Malkin; R.V. Yusupov; M.N. Popovа (Optical Materials: X, 2022)
Comprehensive spectroscopic, magnetization, and theoretical studies of a LaAlO3:Tm3+ single crystal in the ferroelastic R3‾c phase are reported. The Tm3+ ions substitute for the La3+ ions at sites with the D3 symmetry. High-resolution absorption, photoluminescence, and site-selective emission and excitation spectra were measured in the broad spectral range from 4000 to 28000 cm−1 at temperatures 4.2–5 K. The two-fold degeneracy of the ground state of Tm3+ was uncovered by magnetization measurements. Energies and symmetry properties of wave functions of crystal-field levels of the Tm3+ ions were determined and successfully reproduced by crystal-field calculations. Specific profiles with a dip at the center of spectral lines corresponding to transitions involving non-Kramers doublets give evidence for random strains in the studied multidomain sample. The value of 0.1–0.8 cm−1 of deformational splitting of non-Kramers doublets exceeds hyperfine splittings by more than an order of magnitude. The observed line shapes were successfully modeled assuming the interaction of Tm3+ ions with random deformations described by the generalized two-dimensional Lorentzian distribution with the width of (7 ± 0.5)⋅ 10−4. The simulation was performed using the electron-deformation coupling constants calculated in the framework of the exchange-charge model.